ASHABU AL-SABT DALAM AL-QUR'AN (Studi Komparasi Penafsiran Ibn Kathir dan Wahbah Zuhaili) - Jaelani dan Ihwan Amali (Program Studi Ilmu Al-Qur'an dan Tafsir, Institut Agama Islam Negeri (IAIN) Palu, 2021)
As a guide to human life, the Qur'an has served many wise stories about the ancients so that we can make i'tibar in everyday life. One interesting story to study is the story of Ashab al-Sabt. The mufassir, both classical and contemporary mufassir, have their own interpretation in interpreting the story of Ashab al-Sabt contained in the Qur'an, even in interpreting the form of adzab in the story cendrung give rise to a polemic of prolonged interpretation. This research will describe the interpretation of Ibn Kathir and Wahbah al-Zuhaili on the story of Ashab al-Sabt and the similarities and differences between the interpretation of Ibn Kathir and Wahbah al-Zuhaili about Ashab al-Sabt. The approach used is qualitative approach with the type of literature research (library research). As for the results of this study, Ibn Kathir and Wahbah al-Zuhaili interpreted the story of Ashab al-Sabt as the story of the ancient people who lived on the outsized sea of Qazlum (red sea) of Ailah city who violated God's command not to catch fish on Saturday. Second, there is an equal interpretation between the two is that the form of God's curse on Ashab al-Sabt who committed violations in the form of physical curses that is the change of physical form into apes and the two mufassir agreed that in response to the agreement made, Ashab al-Sabt divided into three groups, namely: groups that commit violations, groups that prohibit violations and groups that are silent. The difference in interpretation between the two is that the interpretation of Wahbah al-Zuhaili is ahkam interpretation, this is seen when he interprets the story from the perspective of Fiqh al-Hayah wa al-Ahkam, that the story of Ashab al-Sabt part of the assertion of sadd dzara'i and the obligations of charity ma'ruf and nahi munkar.